PENGAWASAN BADAN LINGKUNGAN HIDUP KABUPATEN GRESIK TERHADAP PERUSAHAAN PENGHASIL LIMBAH BAHAN BERBAHAYA DAN BERACUN (B3) - Ushudi, Al (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
Environmental Law Number 32 of 2009 concerning Environmental Protection and Management explains that the management of Toxic and Hazardous Waste is aimed at maintaining the quality of environmental preservation so that no environmental pollution is carried out by business actors. The purpose of this study is to examine the implementation of the Environmental Law with supervision, enforcement and licensing mechanisms for companies producing B3 waste and resolving disputes through the courts, out of court and public lawsuits. This research data includes primary and secondary data. Library Materials are obtained from reference books, Legislation, Journals, official documents, the internet and other library materials related to Toxic and Hazardous Waste. The results of this study resulted that the Environmental Agency has the authority to give sanctions or revoke permits for companies that carry out environmental pollution and actions taken by the Gresik Regency Environmental Agency in carrying out supervision of companies that produce toxic waste materials, take action against companies that carry out pollution, mechanism procedures enforcement, implementation of pollution recovery, this research also provides an understanding of Administrative, Civil and Criminal sanctions. The role of the community that carries out lawsuits through the courts, outside the courts and the role of environmental organizations in participating in monitoring and carrying out lawsuits against environmental pollution actors.